Analysis of Digital Life Effect of Residents' Trust Based on Multivariate Discrete Choice Model. (18th July 2022) - Zeng, Fan; Cao, Xiao; Zhang, Huan-Ming
Abstract : In view of the impact of digital life on residents' trust, firstly, based on the data of China Household Finance Survey (CHFS), this paper analyzes the change of residents' trust in the era of data flooding. Through basic research and marginal effect analysis, it is found that digital life enhances residents' trust. Secondly, the robustness of the conclusion is confirmed by constructing a series of models such as ordered probit of instrumental variable (IV-O probit), ordered probit of propensity score matching method (PSM-O probit), and ordered probit Heckman (O-probit-Heckman). Finally, through the mechanism test, it is concluded that digital life can enhance residents' trust by increasing social activities and forming an inclusive social environment. It will also increase trust by obtaining information and increasing their cognitive level. The conclusion that digital life can enhance residents' trust is more prominent among urban residents, nonpoor Hukou residents, and Han residents. Further research shows that the breadth and depth of digital life have a positive impact on residents' trust, and digital life can improve residents' risk tolerance.